"Be tough, never let them see what it does to you": towards an understanding of the emotional lives of economic migrants. (6th May 2010) - Lee-Treweek, Geraldine
Geographical movement necessarily brings with it myriad emotions and experiences for those relocating. The work migrants do in the UK is, in the main, low paid and low status, requiring considerable emotional management and self-control (Ehrenreich and Hochschild, 2003). Also, migrants often experience neighbourhood and work place rejections and racism. This paper begins to map the emotional worlds of new Polish migrants in a small town in the North West of the UK ('Northton'), as they struggle to establish themselves in a working class community. The paper discusses emotional defence strategies deployed by participants and the tendency towards emotional containment.